Sul Leibniz del giovane Marx - Simone Cabibbo Giuseppe Cospito (Bollettino Filosofico, 2025)
The aim of this study is to propose an interpretation of the excerpts compiled by Marx in 1841 from the second volume of Leibniz’s Opera omnia, edited by Dutens. Beginning with a parallelism between the excerpts and the original text, following the model developed by Matheron for Marx’s notes on Spinoza, it advances an interpretative hypothesis that connects these materials to Ludwig Feuerbach’s Darstellung, Entwicklung und Kritik der Leibnizschen Philosophie, published in 1837. The underlying assumption is that Marx composed these notes not only on the basis of Hegel’s Lectures on the History of Philosophy, edited by Karl Ludwig Michelet between 1833 and 1836, but mainly under the influence of Feuerbach’s work, thereby advancing a dialectical and de-theologizing reading of Leibniz’s monadology. Keywords: Feuerbach, Hegel, History of Philosophy, Leibniz, Young Marx